The Poltical Speech and the Electronic Cartoon: an Analysis in the Light of Socio-Discursive Interactionism - Abreu-Tardelli, Lília Santos; Santos, Andressa Cristiane dos; Borges, Leticia Fonseca; Ciceri, Natalia Santos (Linha D'Água, 2016)
Based on socio-discursive interactionism (BRONCKART, 1999), this article aims at analyzing from the concept of text layering, emphasizing voices and modalization, the political speech pronounced by Dilma Roussef in the opening of 68th UN General Assembly. In addition, it will be showed how these voices reverberate in other texts, starting from the analysis of an electronic cartoon related to this speech. The speech pronounced by the president in this occasion, is due to the fact that Brazilian media highlighted it, mainly because of the demonstration of the president in relation to north American spying that Brazil experienced. The electronic cartoon was chosen because the genre is related to current facts, essentially critical and polyphonic (ROMUALDO, 2000) and its signification is built related to political facts. The analysis of the president speech enabled us to verify how enunciative mechanisms contribute to the construction of an ideological image of the event itself, of concomitant political events and of the president. Analyzing the cartoon, we point the dialogical relationship of the texts, starting from verbal and non-verbal elements; and, due to the irony, feature of the genre, we notice the text guide the reader to a single point of view of Brazilian political situation.